Предмет: Алгебра,
автор: lakera
Упростите выражение (с решением)
(√(x)+1)(√(x)-1)-2(x-3)
(√(a)+√(b))(√(b)-√(a))-5(a-b)
(√(p)+√(2))²-(p+2)
(√(a)-√)3))²+(√(a)+√(3))²
Заранее спасибо!
Ответы
Автор ответа:
0
1) = x-1-2x+6 = 5-x
2) = b-a-5a+5b = 6b-6a
3) = p+2√(2p)+2-p-2 = 2√(2p)
4) = a-2√(3a)+3+a+2√(3a)+3 = 2a+6
2) = b-a-5a+5b = 6b-6a
3) = p+2√(2p)+2-p-2 = 2√(2p)
4) = a-2√(3a)+3+a+2√(3a)+3 = 2a+6
Похожие вопросы
Предмет: Биология,
автор: asamilohina
Предмет: Биология,
автор: borkovaksenia2007
Предмет: Қазақ тiлi,
автор: milana20072802
Предмет: Алгебра,
автор: հրեջտակ
Предмет: Химия,
автор: maxmoihanov